Soviet pedagogy and the American Educators (1957-1965) - Somogyvári, Lajos (Rivista di Storia dell’Educazione, 2018)
After the Sputnik shock (1957) a definite shift could be observed in the public pedagogical discourses of the United States. Having compared the Soviet and American education it gave the possibility (or a promise) to understand the reasons of the supposed communist superiority, which was confirmed by the technical success of the Soviet Union. This paper tries to describe a special field of the Eastern-Western relations in the Cold War: effects of the Soviet pedagogy in the United States, between 1957 and 1965. The reaction was mainly appreciative; the Soviet representatives and articles also appeared in the international organisations (UNESCO, associations of comparative education) and publications. We can analyse the reception of the Soviet pedagogy on four different levels, using various sources. First, by the articles and books related to the UNESCO, the Soviet educators could enter into the international community of scientists, which was a new development after 1945. The reports of the US delegations about the visitations in the Soviet Union showed the importance of this topic on the next level, the governmental sphere. The third stage will be constituted by the works of the academic sphere (representatives of the universities and institutions); and at the end, a book and a journal will give an example how the Soviet pedagogy formed the public opinion in the United States. The basic corpus of this paper is established by the contemporary publications (articles, books, essays, etc.) in the Western hemisphere, and the official reports of the US administration.